PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PENGUNGKAPANCORPORATE SOCIAL RESPONSIBILITY - Imelda Dharma Wilangga, - (2020)
This research was conducted to examine the effect of the variable Profitability, FirmpSizepand Leverage on Corporate Social Responsibility Disclosure. The sample in this research amounted to 64 Manufacturing Companies listed on the Indonesia Stock Exchange in the 2016-2018 period that were pselected using cluster sampling. The analysis techniquetused is Multiple Linear Regression Analysis using SPSS with a significant level of 5%. The results of this research indicate that (1) Profitability has no effect on Corporate Social Responsibility Disclosure (2) Firm size has now effect on Corporate Social Responsibility Disclosure (3) Leverage=has noreffect on Corporate Social Responsibility Disclosure.